Sn4+ and S2− co-doped N–TiO2−x nanoparticles for efficient and photocatalytic removal of contaminants. Issue 14 (3rd July 2020) - He, Jiahui; Ye, Jin; Ge, Kai; Cao, Jiayu; Fu, Congcong; Li, Zhenxing; Zhang, Yue; Yang, Yongfang
Abstract : N–TiO2− x nanoparticles (NPs) were selected as a basic construction unit because there are many Ti 3+ and O vacancies on its surface. Abstract : N–TiO2− x nanoparticles (NPs) were selected as a basic construction unit because there are many Ti 3+ and O vacancies on its surface. When S 2− and Sn 4+ are co-doped into the N–TiO2− x lattice, the O 2− and Ti 4+ atoms can be replaced, respectively. The formation of dopant energy levels from Sn 4+ and S 2− in Sn 4+ /S 2− /N–TiO2− x causes an obvious red shift to the visible light region. The recombination rate of the e − /h + pairs was significantly reduced due to the fast migration and separation of the electrons as a result of the energy level doping from Sn 4+ and S 2− and the formation of electron traps with Sn 4+ . The N–TiO2− x NP band gap was significantly narrowed from 3.07 eV to 0.77 eV upon co-doping with Sn 4+ and S 2−, resulting in the superior photocatalytic activity of the Sn 4+ /S 2− /N–TiO2− x NPs. The photocatalytic reduction rate of Cr(vi ) increased by 11.6 times and the photodegradation rate of doxycycline hydrochloride (DH) achieved about 5.7 times that of the original N–TiO2− x NPs. This study provided a simple approach to preparing metal and non-metal co-doped N–TiO2− x NPs, which could greatly improve the removal efficiency of contaminants via their synergistic effect.